Dental considerations in a paediatric patient with Diamond-Blackfan anaemia. Issue 9 (14th September 2020) - Azam, Imam; Rahul, Morankar; Tewari, Nitesh; Bansal, Kalpana
Abstract : Diamond-Blackfan anaemia (DBA) is a rare genetic disorder characterised by a decrease in the production of red blood cells due to bone marrow malfunction. The estimation of disease occurrence is approximately 1 in 100 000–2 00 000 live births. This paper presents the case of a 7-year-old male child diagnosed with DBA at the age of 4 months. The diagnosis was established with haematological findings, bone marrow biopsy and molecular testing. The case was managed successfully for dental symptoms without any complication.